Sir Frederic Still (1868–1941): the father of British paediatrics. Issue 4 (21st June 2006) - Dunn, P M
Abstract : As a pioneer of full time paediatrics, as the first professor in this new discipline, and as inaugural president of the British Paediatric Association, Still has been called with justice the father of British paediatrics.